Camino del Sol : Fifteen Years of Latina and Latino Writing - González, Rigoberto (Book collections on Project MUSE., 2010)
From the Publisher: Celebrates fifteen years of Latina literature by bringing together some of the series' best work, including selections from award-winning books by Richard Blanco, Diana Garcia, Luis Alberto Urrea, Pat Mora, Kathleen Alcala, Sergio Troncoso, and Kathleen de Azevedo-plus other prominent writers such as Ray Gonzalez, Francisco Alarcon, and Juan Felipe Herrera. Includes poetry, fiction and nonfiction.